2019
DOI: 10.1007/s10551-019-04380-9
|View full text |Cite
|
Sign up to set email alerts
|

Articulating Values Through Identity Work: Advancing Family Business Ethics Research

Abstract: Family values are argued to enable ethical family business conduct. However, how these arise, evolve, and how family leaders articulate them is less understood. Using an 'identity work' approach, this paper finds that the values underpinning identity work: (1) arise from multiple sources (in our case: religion, culture and sustainability), (2) evolve in tandem with the context; and, (3) that their articulation is relational and aspirational, rather than merely historical. Prior research mostly understood famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 72 publications
0
23
0
2
Order By: Relevance
“…This research thus contributes also to the debate around family legacy, suggesting that religion might be an important component of the social legacy that the owning family perpetuates from generation to generation (Hammond et al, 2016). Dielemann and Koning (2020) also use time as a central dimension in their investigation of how one leader's religious and business identities have co-evolved and merged over time. Using rhetorical analysis, and adopting an identity work approach, they find that the values of one second-generation Chinese-Malaysian Christian business leader are rooted in religion, culture and sustainability, and that the way in which these values are expressed is highly contextual, relational and aspirational, rather than (as previously assumed) historical.…”
Section: Value Formation Preservation Imprinting and Identity Formationmentioning
confidence: 91%
See 1 more Smart Citation
“…This research thus contributes also to the debate around family legacy, suggesting that religion might be an important component of the social legacy that the owning family perpetuates from generation to generation (Hammond et al, 2016). Dielemann and Koning (2020) also use time as a central dimension in their investigation of how one leader's religious and business identities have co-evolved and merged over time. Using rhetorical analysis, and adopting an identity work approach, they find that the values of one second-generation Chinese-Malaysian Christian business leader are rooted in religion, culture and sustainability, and that the way in which these values are expressed is highly contextual, relational and aspirational, rather than (as previously assumed) historical.…”
Section: Value Formation Preservation Imprinting and Identity Formationmentioning
confidence: 91%
“…For example, how do the family's religious and spiritual orientation and beliefs affect how children are raised and how future owners are developed, how the family contends with intra-family conflict, or how goals are developed and infused in the organization? Barbera et al (2020) and Dielemann et al (2020) allude to the mechanism of values imprinting on the business identity as well as next generation members in faith-led family organizations, which may be a good starting point for further research in this area.…”
Section: The Family Systemmentioning
confidence: 99%
“…1). Overall, this is an important step to bridge the two perspectives of identity and ethical behavior (Dieleman and Koning 2020). Second, we add to the rich existing theoretical literature on identity work.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…With our study, we also extend the findings of Vazquez (2016), who identified three critical aspects of ethical behavior in family firms: "involvement of the owning family, socioemotional wealth, and typical social interaction" (p. 705). Moreover, we connect to Dieleman and Koning (2020), who were among the first to bridge identity work and (un)ethical behavior in the context of family firms. We also expand past research that often investigated the individual employee or the organizational context of family businesses in isolation (Treviño et al 2006).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation